RELATION OF TIME BUDGET PRESSURE BY DYSFUNCTIONAL BEHAVIOUR AND ITS INFLUENCE TO AUDIT QUALITY - CHRISTINA SOSOSUTIKSNO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2005)
This study examine the relation of time budget pressure by dysfunctional behaviour which mirror from behaviour of premature sign-off, under-reporting of time, and audit quality reduction behavior and its influence to audit quality.The respondents are senior auditors at BPK and BPKP. Data for the study were collected from 1 BPK and 3 BPKP. The sampling method used is purposive sampling. In total 220 questionnaires were distributed, 130 can be used in analysis, for response rate of 74 percent. Using structural equation modelling of AMOS (Analysis of Moment Structure) Program, the result of this study indicates that time budget pressure has positive influence to behavior of premature sign-off, under reporting of time, and audit quality reduction behavior. By contrast, dysfunctional behaviour which mirror from behavior of premature sign-off, under-reporting of time and audit quality reduction behavior do not have influence to audit quality. Behavior of premature sign-off has positive influence to audit quality reduction behavior.